Valuing Desired Financial Behavior, Accounting Literacy as the Predictors of Financial Behavior of Street Vendors - Hossain, Saif; Yaacob, Abu Sofian; Yusoff, Wan Fadzilah Wan; Rahman, Md. Mizanur (Journal of Entrepreneurship, Business and Economics; Vol 13 No 2 (2025), 2025)
The lack of formal education and low accounting literacy of street vendors in Bangladesh negatively affects their financial behavior. Thus, the fundamental objective of this study is to investigate the predictors (accounting literacy and valuing desired financial behavior) of the financial behavior of street vendors in the capital city of Bangladesh (Dhaka). Using a cross-sectional research design and convenience sampling technique, and after considering missing values, outliers, and multicollinearity, 385 respondents (street vendors) were our final sample size. The findings showed that accounting literacy positively impacts the financial behavior of street vendors. However, valuing desired financial behavior has no moderating effect on the relationship between accounting literacy and financial behavior.  This advocates that government and non-government financial institutions and professionals should focus on improving accounting literacy and the practical accounting abilities of the informal street vendors. Research Paper Keywords: Accounting literacy, financial behavior, financial wellbeing, informal economy, street vendors Reference to this paper should be made as follows: Hossain, S., Yaacob, A.S., Yusof, W.F.W., & Rahman, M.M. (2025). Valuing Desired Financial Behavior, Accounting Literacy as the Predictors of Financial Behavior of Street Vendors. Journal of Entrepreneurship, Business and Economics , 13 (2), 54–83.